PERSONALITY’S INFLUENCE ON THE FORMATION OF A CIVIL SOCIETY IN UKRAINE - Луговська, О. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is dedicated to a clarification of any perspectives for developing values and personality’s influence on the formation of a civil society in Ukraine.